Understanding the effectiveness of attachments in clear aligner therapy: navigating design, placement, material selection and biomechanics - Demir Gizem Boztaş (Sciendo, 2024)
Clear aligner treatments have gained popularity due to their aesthetic advantages over traditional metal brackets. Attachments play a crucial role in enhancing the efficacy of treatment by addressing challenges posed by the flexibility of aligner materials. This comprehensive review aims to clarify the significance of attachments used during clear aligner therapy and explore the nuances of their design, placement, and material selection.